1994
DOI: 10.1002/acp.2350080602
|View full text |Cite
|
Sign up to set email alerts
|

Expert performance in solving word puzzles: From retrieval cues to crossword clues

Abstract: Crossword enthusiasts were first classified as expert or intermediate on the basis of their performance with a previously unseen set of clues, and then participated in five laboratory experiments designed to capture different aspects of their skilled performance: experiment 1 required the generation of words from a fixed set of letters; experiment 2 monitored the solution of anagrams; experiment 3 required the comipletion of a word of given meaning with only three letters presented; experiment 4 was a lexical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
18
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 14 publications
1
18
0
Order By: Relevance
“…How effective one is likely to be at solving crossword puzzles can be predicted to a considerable degree from scores on tests of vocabulary and of word generation (Underwood, Diehim, & Batt, 1994). Not surprisingly, proficiency at solving crossword puzzles also correlates positively with skill at anagrams (Underwood et al, 1994;Witte & Freund, 1995).…”
Section: Some Theoretical Questions and Conjecturesmentioning
confidence: 92%
See 1 more Smart Citation
“…How effective one is likely to be at solving crossword puzzles can be predicted to a considerable degree from scores on tests of vocabulary and of word generation (Underwood, Diehim, & Batt, 1994). Not surprisingly, proficiency at solving crossword puzzles also correlates positively with skill at anagrams (Underwood et al, 1994;Witte & Freund, 1995).…”
Section: Some Theoretical Questions and Conjecturesmentioning
confidence: 92%
“…Not surprisingly, proficiency at solving crossword puzzles also correlates positively with skill at anagrams (Underwood et al, 1994;Witte & Freund, 1995).…”
Section: Some Theoretical Questions and Conjecturesmentioning
confidence: 96%
“…Nickerson (1977) observed that crossword puzzles are cued retrieval tasks, and other studies have further suggested that crossword proficiency depends more on the manipulation of letters and word fragments than on knowledge of a large number of words (Underwood, Diehim, & Batt, 1994). Goldblum and Frost (1988) showed that any cluster of three adjacent letters facilitated retrieval better than did dispersed letters.…”
mentioning
confidence: 99%
“…In addition, syllabic clusters facilitated more recall than did nonsyllabic clusters or unpronounceable clusters. For expert crossword solvers, puzzle proficiency could be predicted by word generation from a string of letters, performance on anagrams, sensitivity to a suffix of a word, sensitivity to a pseudosuffix in a word, and vocabulary scores (Underwood et al, 1994). Witte and Freund (1995) further showed that performance on anagramsanother independent test of word retrieval skills-was positively correlated with previous crossword puzzle experience.…”
mentioning
confidence: 99%
“…Correlation analysis revealed that the three major predictors of crossword success were general knowledge, previous crossword puzzle experience, and word-retrieval skills. Underwood, Diehim, and Batt (1994) found that expert crossword solvers' puzzle proficiency was predicted by word generation from a string of letters, performance on anagrams, sensitivity to the suffix of a word, sensitivity to the pseudosuffix of a word, and vocabulary scores.…”
mentioning
confidence: 98%